An Analysis of Servitization Adoption in Chinese Market: A Case Study Approach - Gao, Mingyang (2014)
In order to adjust increasing competitive and economic pressures, more manufacturing companies in developed Western countries have added services to their traditional business models. According to Vandermerwe and Rada (1998), servitization refers to the bundling of products and services, namely the process of creating value by adding services to products. Several multinational manufacturing companies have adopted servitization in their business and invented new business models, such as “TotalCare” and “Power-by-the-hour” in Rolls-Royce and “Equipment Management Services” in Xerox (Baines and Lightfoot, 2013). By reviewing the previous servitization studies, it seems like that servitization has been studied in various disciplines and perspectives. Servitization has research origins from operation management, service management, service marketing, service science and other disciplines (Baines and Lightfoot, 2013). Several studies examine servitization from value creation perspective (Smith et al., 2014), organizational perspective (e.g. Pawar et al., 2009) and supply chain relationship perspective (e.g. Braziotis and Tannock, 2009). However, according to the author’s acknowledgement, it seems like that no servitization study about emerging economy has been published currently. The aim of this study is to examine servitization adoption level in mainland China. Three research questions are developed, including the business context of servitization, servitization from a strategic level and from a tactical level. This dissertation adopts qualitative research method and in-depth interviews to answer these research questions. Multiple case studies are conveyed by recruiting six participants from three Caterpillar Chinese official dealers and one Chinese high-speed train customer. Some key findings are identified in within-case analysis and cross-case analysis. Some findings and theories like servitization adoption situation in China, suitable industrial characteristics for adopting servitization and manufacturers’ strategies to adopt servitization are critically discussed and analyzed. It concludes that the current servitization adoption level in China is low.